Assessment of the Economic Background of the OBOR. Issue 2 (31st August 2017) - Cheong, Inkyo
Abstract : Although there is a growing number concerning articles/papers on China's 'One Belt, One Road' (OBOR), it is difficult to find comprehensive research regarding the economic background in spite of the OBOR initiative involving multi-dimensional considerations. Although China targets to become a soft power leader by reviving the spirit of the old Silk Road, the OBOR is a large-scale investment project, whose rate of investment (ROI) is important for sustainability. Since new infrastructure in isolated regions is likely to be used less frequently, anticipated profitability is low. In spite of this risk, China promotes the OBOR for its economic and political purposes. China will promote the OBOR in spite of the U.S. withdrawal from TPP membership, since boosting aggregate demand is of critical importance for the country. This paper analyzes the economic background of the OBOR, which establishes China's own model of regional integration, eases unemployment, and internationalizes its currency. Finally, this paper discusses diverse risks for China in the process of implementing the OBOR.